BRAND EQUITY SEBAGAI PEMBENTUK KEPUTUSAN PEMBELIAN MELALUI PURCHASING INTENTION PADA KONSUMEN SEPEDA MOTOR - Jatmiko, Jatmiko (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Purpose of research after obtained model of Decision of Purchasing in creative motorcycle industry based on brand equity, hence research at next stage which is to be achieved is Construction method and marketing strategy for company in creative motorcycle industry that able to push decision purchase based on brand equty, so useful to develop appropriate strategy policies to increase sales turnover. The application of a marketing strategy formed through a customer purchase decision-making model based on customer equity, is the most valuable asset in business, serves as the foundation that will shape the image, personality, identity, attitudes, familiarity, association and awareness of a product. This research design using triangulation method approach that is combination of quantitative and qualitative analysis. The population in this study is all consumers of motorcycles in Indonesia who buy and use motorcycles. Of this population will be drawn samples to be used in research as respondents as much as 300 respondents. Sampling technique in this research using non probability sampling method with quota sampling method. The analytical method used is SEM with AMOS, resulting in a model which is a representation of the theory analyzed descriptively. From the results of model testing was developed to develop competitive strategy according to the condition of product / company of creative industry concerned by using BCG Matrix, ADL Matrix, and PLC Matrix. The result of the research in model testing shows that the variable of Perceived Quality, Brand Loyalty, Brand Awareness, have significant influence to Decision Purchasing, which is mediated by Intention Purchasing. While the Brand Association does not affect Intention Purchasing and Decision Purchasing. Intention purchasing, able to mediate between Brand Awareness, Percived Quqlity, Brand Loyality to the purchase decision. Based on the purchasing decision formulation, the competitive strategy is mapped based on the life cycle stages of introduction, growth, maturity, and decline to the competitive position of industry through company level including weak, tanable, favorable, strong, and dominant. Keyword : brand equity, purchasing intention, purchasing decision.